Carbon-based Nanomaterials for Delivery of Small RNA Molecules: A Focus on Potential Cancer Treatment Applications - Habib, Saffiya; Singh, Moganavelli (Pharmaceutical Nanotechnology, 2022)
Background: Nucleic acid-mediated therapy holds immense potential in treating recalcitrant human diseases such as cancer. This is underscored by advances in understanding the mechanisms of gene regulation. In particular, the endogenous protective mechanism of gene silencing known as RNA interference (RNAi) has been extensively exploited. Methods: We review the developments from 2011 to 2021 using nano-graphene oxide, carbon nanotubes, fullerenes, carbon nanohorns, carbon nanodots and nanodiamonds for the delivery of therapeutic small RNA molecules. Results: Appropriately designed effector molecules such as small interfering RNA (siRNA) can, in theory, silence the expression of any disease-causing gene. Alternatively, siRNA can be generated in vivo by introducing plasmid-based short hairpin RNA (shRNA) expression vectors. Other small RNAs, such as micro RNA (miRNA), also function in post-transcriptional gene regulation and are aberrantly expressed under disease conditions. The miRNA-based therapy involves either restoration of miRNA function through the introduction of miRNA mimics; or the inhibition of miRNA function by delivering anti-miRNA oligomers. However, the large size, hydrophilicity, negative charge and nuclease-sensitivity of nucleic acids necessitate an appropriate carrier for their introduction as medicine into cells. Conclusion: While numerous organic and inorganic materials have been investigated for this purpose, the perfect carrier agent remains elusive. Carbon-based nanomaterials have received widespread attention in biotechnology recently due to their tunable surface characteristics and mechanical, electrical, optical and chemical properties.
Keywords: small RNA